Soil ecosystem services in urban areas and methods for their assessment using remote sensing - Poreba, Ludwika; Glowienka, Ewa; Siebielec, Grzegorz (Frontiers in Environmental Science, 2026)
Cities and nature are interdependent. Many of the needs of urban population are fulfilled by ecosystem services, which are typically grouped into four categories: provisioning, regulating, habitat, and cultural services. These include such benefits as food and water supply, climate regulation, biodiversity support, as well as various cultural and recreational values. Soil, through its functions, is an important element of the environment that provides ecosystem services in urban areas. This publication focuses on a review of the literature on soil ecosystem services, with particular emphasis on the urban context. It also highlights how remote sensing tools and spatial planning approaches can be applied to monitor soil ecosystem services in cities and support sustainable urban management. The increasing level of urbanization poses a major threat to soil and its ability to provide ecosystem services. Urbanization worsens climatic conditions in cities, threatens biodiversity by interrupting ecological corridors, increases surface runoff creating flood risks, and contributes to elevated levels of pollution in both soil and air. Given that this process is inevitable, minimizing environmental damage requires well-designed land management approaches. Integrating ecosystem services into urban planning will not only contribute to preserving nature in the best possible condition, but will also enhance the quality of life for city dwellers.